Jizya in the modern state - Abdel-Azim, Ahmed Fathi (Journal of Islamic Sciences, 2025)
The research aims to demonstrate the purity and supremacy of Islam, far from injustice. Islam does not unjustly take money from anyone. Rather, Islam takes money rightfully and deals with it in the most refined and beneficial manner. The research also aims to demonstrate the jurists’ guidance on cases of taking jizya. The researcher adopted the methodology of incomplete induction of the jurists’ opinions on jizya, while attempting to apply them to contemporary reality. The research has three axes: defining jizya and its history, then detailing scholars’ interpretation of jizya. One of the most important results is that jizya is a financial obligation taken from dhimmis when conditions stabilize, just as Muslims pay zakat, which contributes to meeting people’s needs in society. Non-Muslims can choose to name the money they pay, whether it is zakat, tax, or jizya. The important thing is that they contribute a portion of their money to what society needs, such as building schools, hospitals, etc..